Use of electronic media in health promotion: is it cost effective? - Yahya, B., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
It is common knowledge that the evaluation of the effectiveness and impact of health promotion input is extremely difficult to measure compared to other activities and programmes. An intangible product such as health seldom can be tried out. With regards to promotion, all educational tools have limitations or shortcomings and this is why a multi-strategy approach is usually advocated. Its success is a measure of the effectiveness of these multiple strategies which include social marketing techniques using multi-faceted media such as TV/radio messages focusing on the general population as well as specific target groups.A few internationally recognised marketing and research companies were commissioned to evaluate the overall effectiveness of the Healthy Lifestyle Campaign Phase 1. For example, the ten half - hour episodes on topics related to healthy eating were aired on TV1, every Sunday at 1l.30 am starting from 6th July 1997. A total 1.55 million persons viewed the episode series ranging from 83,000 viewers (3rd July 1997) to 273,000 viewers (31st July 1997). The production cost for the series came to a total of RM340, 000, i.e. at an average of 21.9 cents per person. In addition, the 10 episodes can be repeated over TV as well as can be used for repeated video screenings in all hospitals and health centres.Thus, there are evidences to suggest that electronic media approach is more effective and successful than other approaches. It is also more effective and successful in reaching target groups.